1995
DOI: 10.1101/gr.5.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Genes and languages in Europe: an analysis of mitochondrial lineages.

Abstract: When mitochondrial DNA sequence variation is analyzed from a sample of 637 individuals in 14 European populations, most populations show little differentiation with respect to each other. However, the Saami distinguish themselves by a comparatively large amount of sequence difference when compared with the other populations, by a different distribution of sequence diversity within the population, and by the occurrence of particular sequence motifs. Thus, the Saami seem to have a long history distinct from othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
132
2
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(144 citation statements)
references
References 21 publications
(12 reference statements)
8
132
2
2
Order By: Relevance
“…A similar pattern is detected within the U5a haplogroup with the highest diversity in Northeast Europe (0.930 ± 0.015), followed by Northwest Siberia (0.713 ± 0.083) and South Siberia (0.524 ± 0.209). By contrast, the Northeast European U5b subhaplogroup, including the U5b1b1 'Saami motif', 25,29 was not observed among Northwest Siberians except the Samoyedic-speaking Nganasan (1.9%). The U7 subhaplogroup was found only among the Northwest Siberian Khanty (14.2%) and Mansi (3.2 -5.1%), Central Asian Uighur (4.2%) and Northeast European Finns (0.5%).…”
Section: Genetic Relationships Among the North Eurasian Populationsmentioning
confidence: 83%
See 2 more Smart Citations
“…A similar pattern is detected within the U5a haplogroup with the highest diversity in Northeast Europe (0.930 ± 0.015), followed by Northwest Siberia (0.713 ± 0.083) and South Siberia (0.524 ± 0.209). By contrast, the Northeast European U5b subhaplogroup, including the U5b1b1 'Saami motif', 25,29 was not observed among Northwest Siberians except the Samoyedic-speaking Nganasan (1.9%). The U7 subhaplogroup was found only among the Northwest Siberian Khanty (14.2%) and Mansi (3.2 -5.1%), Central Asian Uighur (4.2%) and Northeast European Finns (0.5%).…”
Section: Genetic Relationships Among the North Eurasian Populationsmentioning
confidence: 83%
“…Two sequences were excluded: an L2 sequence in the Norwegian sample 27 and one sequence with unclear haplogroup definition in the Karelian sample. 25 The approximate locations of all the 42 mtDNA population samples used in this study are shown in Figure 1a.…”
Section: Khanty and Mansi Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to samples typed by the authors for this study, the following previously published mtDNA HVS1 sequences were used: 398 Icelanders (Helgason et al, 2000b), 551 Icelanders (Helgason et al, 2003), 39 Icelanders (Sajantila et al, 1995), 78 Orkney Islanders (Helgason et al, 2001), 664 inland Scots (Helgason et al, 2001), 216 northwestern coastal Scots (Helgason et al, 2001), 226 inhabitants from the Western Isles and the Isle of Skye (Helgason et al, 2001), 105 Irish (Richards et al, 2000), 216 Norwegians (Opdal et al, 1998), 324 Norwegians (Helgason et al, 2001), 74 Norwegians (Passarino et al, 2002), 28 Swedes (Kittles et al, 1999) and 32 Swedes (Sajantila et al, 1996). The following previously published Y-chromosome haplotypes were also used: 181 Icelanders (Helgason et al, 2000a), 12 Danes (Helgason et al, 2000a), 221 Irish (Helgason et al, 2000a), one Irish (Hurles et al, 1999), 110 Norwegians (Helgason et al, 2000a), two Norwegians (Hurles et al, 1999), 78 Norwegians (Wilson et al, 2001), 71 Orkney Islanders (Wilson et al, 2001) and 109 Swedes (Zerjal et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…14 Several genetic studies have been conducted to shed light on the genetic origin of the Saami. [15][16][17][18] These studies suggested that the Saami are descendants of Europeans who, several thousand years ago, reached northern Fennoscandia from both a western and an eastern route and subsequently got admixed. They also found a small East Asian contribution to the gene pool.…”
Section: Introductionmentioning
confidence: 99%